2004
DOI: 10.1182/blood-2003-12-4384
|View full text |Cite
|
Sign up to set email alerts
|

Apparent modulation of CD20 by rituximab: an alternative explanation

Abstract: We read with interest the paper from Jilani et al 1 in which rituximab treatment appeared to down-modulate CD20 expression through a combination of internalization and RNA regulation. The result is unexpected because previous studies had shown that CD20 is not modulated by monoclonal antibody (mAb) treatment, 2-4 even in vivo. 5 The study by Jilani et al used an anti-mouse immunoglobulin polyclonal antibody (Ab) that binds to the mouse V regions in rituximab. This reagent will bind to rituximab, while the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
1
16
1
Order By: Relevance
“…In the first, since CD79a expression is known to precede CD19 or CD20 expression in the earliest differentiation events of B-cell ontogeny [15,16], it is possible that the CD79a + CD20 ) immature B cells, which are not susceptible to RIT, were residual in the spleen. Previous studies [8,9] [17,18] have demonstrated the possible internalization of CD20 epitopes after RIT administration; it has also been suggested that RIT can mask CD20 epitopes, resulting in false negative expression of CD20 in FACS analysis of B cells in peripheral blood, as FACS analysis can detect only extracellular epitopes. However, B cells express not only extracellular CD20 epitopes but also intracellular CD20 epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…In the first, since CD79a expression is known to precede CD19 or CD20 expression in the earliest differentiation events of B-cell ontogeny [15,16], it is possible that the CD79a + CD20 ) immature B cells, which are not susceptible to RIT, were residual in the spleen. Previous studies [8,9] [17,18] have demonstrated the possible internalization of CD20 epitopes after RIT administration; it has also been suggested that RIT can mask CD20 epitopes, resulting in false negative expression of CD20 in FACS analysis of B cells in peripheral blood, as FACS analysis can detect only extracellular epitopes. However, B cells express not only extracellular CD20 epitopes but also intracellular CD20 epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have reported that CD20 did not substantially modulate from Raji BL cells or a primary CLL sample in a short-term 2-hour culture. 45 To clarify these apparent discrepancies, we determined to study modulation on a variety of B-cell targets. Michel and Mattes have previously demonstrated the internalization of CD20 on certain human B-cell lines after mAb engagement but found it to be slow with little internalization until 18 hours.…”
Section: Cd20 Mabs Rapidly Internalize and Are Targeted To The Lysosomentioning
confidence: 99%
“…10,15,16 There have been a wide variety of MRD flow assays reported and most rely to some extent on assessment of CD20 expression, which may be compromised during rituximab therapy. [19][20][21] In order to allow direct comparison of the different approaches, it is necessary to develop a consensus reagent set that can be used in peripheral blood and bone marrow at all stages of the disease and independent of the therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%